Test-retest reliability of physiological and performance responses to 120 minutes of simulated soccer match play - Harper, L. D.; Hunter, R.; Parker, P.; Goodall, S.; Thomas, K.; Howatson, G.; West, D. J.; Stevenson, E.; Russell, M. (The Journal of Strength and Conditioning Research, 2016)
This study investigated the test-retest reliability of physiological and performance responses to 120 minutes (90 minutes plus 30 minutes extra-time [ET]) of the soccer match simulation (SMS). Ten university-standard soccer players completed the SMS on 2 occasions under standardized conditions. Capillary and venous blood was taken pre-exercise, at half-time, and at 90 and 120 minutes, with further capillary samples taken every 15 minutes throughout the exercise. Core temperature (Tcore), physical (20- and 15-m sprint speeds and countermovement jump height), and technical (soccer dribbling) performance was also assessed during each trial. All variables except blood lactate demonstrated no systematic bias between trials (p > 0.05). During the last 15 minutes of ET, test-rest reliability (coefficient of variation %, Pearson's r, respectively) was moderate to strong for 20-m sprint speed (3.5%, 0.71), countermovement jump height (4.9%, 0.90), dribble speed (2.8%, 0.90), and blood glucose (7.1%, 0.93), and very strong for Tcore (1.2%, 0.99). Moderate reliability was demonstrated for 15-m sprint speed (4.6%, 0.36), dribble precision (11.5%, 0.30), plasma insulin (10.3%, 0.96), creatine kinase ([CK] 28.1%, 0.38), interleukin-6 (24%, 0.99), nonesterified fatty acids ([NEFA] 13.2%, 0.73), glycerol (12.5%, 0.86), and blood lactate (18.6%, 0.79). In the last 15 minutes of ET, concentrations of blood glucose and lactate and sprint and jump performances were reduced, whereas Tcore, NEFA, glycerol, and CK concentrations were elevated (p = 0.05). The SMS is a reliable protocol for measuring responses across the full 120 minutes of soccer-specific exercise. Deleterious effects on performance and physiological responses occur during ET.